The effectiveness of a proposed training program to reduce the level of obesity in men (35-51) years -Pilot Study - boujlida, hassene; kassimi, Sofian (sports creativity, 2025)
This study aimed to know the effectiveness of a proposed training program to reduce the level of obesity in men (35-51) years. The research sample consisted of 30 men, all of whom suffer from the problem of overweight, who were deliberately selected from the municipality level of Sidi Mezghish, Skikda State. Every week she urges the researcher's supervision and after implementing the tribal measurements and applying the training program and the dimensional measurements, the researcher reached the following conclusions: - The arithmetic mean for weight and the physical body measurements represented in each of the abdominal circumference, pelvic circumference, and femoral circumference that we performed after three months of applying the program was noticeably reduced, which indicates the effectiveness of the training program applied to reduce